Effect of Perceived Organizational Support and Workload on Employee Performance with Moderation of Person Organization Fit - Siti Maida; Lukiyana Lukiyana (Ekonomis: Journal of Economics and Business, 2024)
The purpose of this study was to investigate and analyze the impact of perceived oganizational support and workload on employee performance with moderation by the individual's organizational fit. The study population included a sample of 43 respondents aged 24-47 who were employees and employees of North Jakarta BNNK. The datasprocessing methodsin thissresearch uses smartPLS for the purpose of hypothesis verification. The resultssof this study show that perceived organizational support has a positive and significant impact on employee performance, and workload has a positive and significant impact on employee performance, and that an individual's organizational fit hassa positive and significant effect on employee performance. positive and significant impact on employee performance, and person organization fit weakens but has an effect and can moderate between perceived organizational support on employee performance, person organization fit is able to strengthen and can moderate the workload on employee performance. This study recommends that if you want to improve employeesperformance, it is advisable to be able to provide psychological differentiation to employees who work, because some of the respondents to this study stated that agencies have not fully providedsgood support, causing employee performance to be less than optimal, but this can be minimized by providing support and rewards to employees.